Direct Imaging for Single Molecular Chain of Surfactant on CeO2 Nanocrystals. Issue 31 (1st July 2018) - Hao, Xiaodong; Chen, Chunlin; Saito, Mitsuhiro; Yin, Deqiang; Inoue, Kazutoshi; Takami, Seiichi; Adschiri, Tadafumi; Ikuhara, Yuichi
Abstract: Organic surfactant controls the synthesis of nanocrystals (NCs) with uniform size and morphology by attaching on the surface of NCs and further facilitates their assembly into ordered superstructure, which produces versatile functional nanomaterials for practical applications. It is essential to directly resolve the surfactant molecules on the surface of NCs to improve the understanding of surface chemistry of NCs. However, the imaging resolution and contrast are insufficient for a single molecule of organic surfactant on NCs. In this work, direct characterization of organic surfactant on CeO2 NCs is conducted by using the state‐of‐the‐art aberration corrected scanning transmission electron microscopy (STEM) imaging and electron energy loss spectra (EELS) techniques. The explicit evidence for the existence and distribution of organic surfactant on CeO2 NCs are obtained on the atomic scale by EELS elemental mapping. Besides, STEM imaging parameters are systematically adjusted and optimized for the direct imaging of a single molecular chain of organic surfactant on CeO2 NCs. Such direct visualization of organic surfactant molecule on the surface of NCs can be a significant step forward in the fields of nanomaterials surface chemistry and materials characterization. Abstract : Direct observation of surfactant molecule on the surface of CeO2 nanocrystals is achieved here. Electron energy loss spectra mapping spectra offer the explicit evidence for the existence and distribution of surfactant on CeO2 nanocrystals (NCs), and the scanning transmission electron microscopy imaging shows the clear contrast of a single molecular chain of organic surfactant on the side of CeO2 NC.